Investigation of Cloud-Effects on Voltage Stability of Distribution Grids with Large Amount of Solar Photovoltaics - Cirjaleanu, Valeriu (My University, 2017)
The Photovoltaic (PV) energy is becoming more and more popular nowadays due to both the awareness of people about environmental concerns and the governmental support schemes which makes it more accessible for the potential PV owners to install PV systems at the residential level. However, the integration of large amount of PV systems at the residential level might bring challenges to the utilities companies regarding the power quality and the reliability of the system. One of the biggest challenges is the power output fluctuation of the PV systems. This fluctuation is caused by the weather condition and especially, by the fast-moving clouds which can be referred as the ’’cloud-effect’’. This project work has investigated the ’’cloud-effect’’ of the solar PV units in a residential grid with regard to voltage stability. The residential network (the real system) is a 10/0.4 kV radial grid located in Mölndal area, Göteborg. The simulations have shown that the Mölndal grid was able to maintain its voltage stability when cloud induced power swings occurred in the network. This outcome can be explained as the distribution network is designed to be a strong grid with high short circuit capacity, short line branches and low load condition during the summer in the Swedish residential houses. However, in order to investigate the potential negative impacts of the cloud induced power swings on another possible weaker residential network, the operational parameters (the short circuit capacity and the load power) of the real system were modified. The simulations have shown that for the modified system, the network was able to maintain its voltage stability for 20-40 % PV penetration levels. For the 50% PV penetration level, cloud induced power swings caused low operational voltage profiles (voltage instability) within the grid. This instability was not properly identified when the loads were modeled as static loads. Therefore, dynamic load models are recommended to be implemented in impact-studies in order to investigate more accurate the PV impact on the system operation, especially when a relatively large amount of the system load is represented by induction motors. Different mitigating solutions were proposed and implemented in the simulation for the modified case scenario. Static Var Compensator, STATCOM and Energy Storage Devices were found to improve the voltage stability limits of the network and therefore, to allow a higher penetration level of PV energy. The simulations have shown that ESD are the best mitigating solutions in order to counteract the PV power drops if they are located in close proximity of the electrical loads. For the case with SVC integration, it was found that the placement and the size of the device has to be correlated with the regulating transformer for proper and reliable operation of the grid. For the case with STATCOM integration, it has been shown that its dynamic transient response was superior to SVC when the network was iv subjected to PV power drops. This difference was due to both, that the device incorporated an inverter which provided reactive power independent of the grid voltage and also that its dynamic control was roughly modeled as for a PV inverter. By using this type of control algorithm, the reactive power support of the device was injected more casually which led to a better transient response within the system.
Keywords: Elkraftteknik; Electric power engineering